Pengembangan Modul Basic Training (Latihan Kader I) Berbasis Digital pada Perkaderan Himpunan Mahasiswa Islam (HMI) Cabang Langkat - Putra, Alwanda; Mardianto, Mardianto; Salminawati, Salminawati (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This study aims to develop and test the feasibility and effectiveness of a digital-based Basic Training module (Latihan Kader I) to support the regeneration process of the Langkat Branch of HMI. The method used is research and development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were obtained through observation, interviews, questionnaires, pre- and post-tests, and documentation, then analysed descriptively using paired t-statistical tests. The validation results showed that the module met the